PELATIHAN MENGHADAPI PERSOALAN DIRI BERBICARA DI DEPAN UMUM IBU-IBU PENGURUS PENGAJIAN DESA KADILANGU, KECAMATAN BAKI, KABUPATEN SUKOHARJO - Giarti Slamet; SWE Handayani; Yanti Sri Danarwati; Christina Nur Wijayanti (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract This community service activity aims to provide guidance to female recitation administrators to practice publis speaking, provide knowledge on how to develop public speaking abilities and skills, speaking skills everyone can appear in public. Ready to carry out so that this training can grow the courage of mothers to be able to appear in public, provide confidence that can affect the success and fluency of public speaking, and train mothers in controlling anxiety, stage fright before speaking in front general. The method used in this training activity includes 3 stages: the preparation stage, the implementation stage, and report preparation stage. The evaluation results in this training provide an opportunity for mothers to practice speaking in front of participants, even though some are still nervous, trembling, and speaking skills can also broaden your network. When you speak in public well, people can be amazed and want to talk to you. This can be a good opportunity to build new relationships to open up various opportunities. For example building a business together and collaborating on certain projects. Keywords: Training, self-problems and speaking